Strategi Pengembangan Agrowisata Jambu Air di Kelurahan Betokan Kabupaten Demak - Nur Fitriyani; Mulyono Mulyono; Khairul Fikri Al Madani (CV. ULIL ALBAB CORP, 2024)
This study analyzes the procedure for creating water apple agrotourism in Betokan Town, Demak Regency. The plan of this exploration is enlightening subjective utilizing SWOT approach examination to plan a few procedures that are valuable for scientists in creating agrotourism of Citra water apple and Delima water apple. The information for this examination are ranchers as water guava cultivators, the public authority and neighborhood networks. The method utilized was inside and out interviews. This study to analyze development strategy for the water apple agrotourism in Demak Regency's which in Betokan Town. The exploration is engaging subjective with SWOT examination to plan a few procedures that can be involved by specialists to foster citra and delima water apple agrotourism. The information assortment method utilized was inside out interviews. The aftereffects of this study make sense of that there are four key advances that can be taken with regards to improvement, for example, normal asset advancement procedures, framework improvement systems, showcasing techniques and collaboration methodologies with accomplices and related parties, specifically neighborhood legislatures, focuses selling delima guava organic product for promoting. outside the Demak region, likewise the job of the local area in presenting and advancing the handled water apple, pomegranate items to the more extensive local area. The execution of these procedures is supposed to affect working on the government assistance of the local area in the citra and delima water apple and development regions and can give schooling to travelers in developing Citra and delima water apples plants which can foster well in the Demak region as well as turned into a symbol of pride for Demak Regency.